Acceptance factors of pneumococcal vaccination among adult population: a systematic review - Siti Nor Mat,; Norzaher Ismail,; Syafiq Taib,; Hasanain Faisal Ghazi,; Zahir Izuan Azhar,; Mohammad Saffree Jeffree,; Azmawati Mohammed Nawi,; Mohd Rohaizat Hassan, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
Introduction : Pneumococcal disease causes considerable morbidity and mortality, including among adults. Adult pneumococcal vaccines help to prevent these burdens, yet, they are underutilized. Our objective is to systematically collect and summarize the available evidence on the potential factors that lead to pneumococcal vaccination acceptance among of adult community.